The impact of different types of anaesthesia on the course of tonsillectomy surgery - Kolesnichenko, V. (Journal of Education, Health and Sport, 2023)
Recurrent tonsillitis is considered to be one of the most common ENT diseases. Tonsillectomy as a method of recurrent tonsillitis’ treatment is being performed as usual as 20% of all surgeries in ENT departments. The critical criteria for the success of tonsillectomy for the surgeon are the frequency of perioperative complications, long-term results of treatment, and the patient’s recovery time. For the patient, those criteria are the severity of pain, psychoemotional stress, the time spent in the hospital, and how quickly he can return to his daily life routine. The factors that significantly affect the outcome of tonsillectomy are the choice of anaesthetic management. Our study aimed to optimise the approach to choosing between endotracheal anaesthesia and local anaesthesia. Clinical studies were made among 158 patients with recurrent tonsillitis who underwent a bilateral tonsillectomy. The patients were divided into two groups. The first group consisted of 97 patients undergoing tonsillectomy using local anaesthesia. The control group included 61 patients undergoing tonsillectomy using endotracheal anaesthesia. We considered the factors such as duration of surgery, the amount of blood loss, intraoperative events, number of incidents of primary and secondary bleeding, assessment of pain syndrome, necessity of analgesics administration, length of hospital stay, and recovery period. Conclusions: tonsillectomy surgery using local anaesthesia requires less time to perform, has less blood loss, fewer intraoperative events, and fewer incidents of primary and secondary bleeding. The average level of pain is higher in patients using endotracheal anaesthesia.